Operational Plan For The Numbers Using Fast Mass Transport Trem In Surabaya - Sapto Budi Wasono; M Zusron Anggik (NAROTAMA UNIVERSITY, Indonesia)
Traffic jams often occur in the city of Surabaya. Due to the increasing population and the desire to have private vehicles, this has led to the need for adequate additional road capacity. However, the frequent increase in road capacity is not enough with the very high growth of road users. Therefore, the Surabaya city government planned an alternative route to reduce the congestion that occurred, one of which was building a rapid mass transportation, the tram, the construction of the tram itself was still in the planning stage, requiring a study of the influence of operational plans on public interest in trams, specifically for motorcyclists. What factors can make motorbike riders divert to the tram. One way to find out how much interest motorbike riders have is to use multiple linear regression methods which require data from road users. Questionnaires are needed to retrieve data and collect samples consisting of 200 respondents. In this study the location of the deployment is in the area that trams are going to plan for, starting from Joyoboo - Jl.Raya Darmo - Urip Sumoharjo - Jl.Basuki Rahmat - Jl.Embong Malang - Jl.Blauran - Jl.Bubutan - Tugu Pahlawan - Jl. Indrapura - Jl. Rajawali. While going south will pass Jl. Heroes - Jl. Gemblongan - Jl, Tunjungan - Jl. Governor Suryo - Jl. Panglima Sudirman - Jl. Urip Sumoharjo - Jl. Raya Darmo - Terminal Joyoboyo